Transvesical natural orifice transluminal endoscopic surgery (NOTES) nephrectomy with kidney morcellation: a proof of concept study - Lima, E (2012)
Study Type - Therapy (case series) Level of Evidence 4. What's known on the subject? and What does the study add? Until now, the transvaginal approach has been the only method of removing larger specimens from the abdominal cavity using natural orifice transluminal endoscopic surgery. There has been no means of extracting larger specimens in men and the means are restricted even in women, particularly in young women. The present study shows that the difficulty of large specimen retrieval can be overcome, irrespective of the diameter of the chosen port, through natural orifices using morcellation. OBJECTIVE: To show, in a porcine model, the feasibility of a complete transvesical natural orifice transluminal endoscopic surgery (NOTES) nephrectomy with kidney extraction after morcellation through the same port. MATERIALS AND METHODS: Transvesical nephrectomy and morcellation were performed in six pigs at Minho University, Braga, Portugal after institutional review board approval. The transvesical port and the cystotomy were created under the guidance of a ureteroscope, while the remaining steps were done under the guidance of an operating telescope. Dissection of the renal vessels and kidney was performed using dissection grasping forceps and a vessel sealing system (LigaSure(™) ; Covidien, Mansfield, MA, USA) and morcellation was done using a Piranha(™) morcellator (Richard Wolf, Knittlingen, Germany). RESULTS: There were no complications related to the creation of transvesical access. The image provided by the telescope was superior to that of the ureteroscope, especially underwater. Morcellation was quick and effective, with the support of a fixing needle through the abdominal wall, designed to fix the kidney, after laceration of a bowel loop occurred in the first experiment.  It was found that technical improvements are needed to ensure safety of NOTES morcellation. CONCLUSIONS: Kidney morcellation after nephrectomy, using a natural orifice exclusively, is feasible.  Despite technical limitations, this proof of concept study can be regarded as a potential step towards the application of NOTES in urology.